Bioresorbable porous β-tricalcium phosphate chelate-setting cements with poly(lactic-co-glycolic acid) particles as pore-forming agent: fabrication, material properties, cytotoxicity, and in vivo evaluation. Issue 1 (31st December 2021) - Ando, Akihiro; Kamikura, Maho; Takeoka, Yuko; Rikukawa, Masahiro; Nakano, Kazuaki; Nagaya, Masaki; Nagashima, Hiroshi; Aizawa, Mamoru
ABSTRACT: Calcium-phosphate cements (CPCs) have been used as bone filling materials in orthopaedic surgery. However, CPCs are set using an acid-base reaction, and then change into stable hydroxyapatite (HAp) in a living body. Therefore, we developed bioresorbable chelate-setting β -tricalcium phosphate ( β -TCP) cements based on surface modifications of inositol phosphate (IP6). In order to improve the bioresorbability, we fabricated IP6/ β -TCP cements hybridized with poly(lactic-co-glycolic acid) (PLGA) particles as a pore-forming agent. The compressive strengths of the cements with the amounts of 5 and 10 mass% PLGA particles were 23.2 and 22.8 MPa, respectively. There was no significant difference from cements without PLGA (23.4 MPa). The setting times of the cement specimens with PLGA particles (30 min) were a little longer than those without PLGA particles (26.3 min). The lack of cytotoxicity of the cement specimens was confirmed using osteoblast-like cells (MC3T3-E1). Cylindrical defects were made by drilling into the tibia of mini-pigs and injecting the prepared cement pastes into the defects. Twelve weeks after implantation the specimens were stained with toluidine blue and histologically evaluated. Histological evaluation of cement specimens with PLGA particles showed enhanced bioresorbability. Newly-formed bone was also observed inside cement specimens with PLGA particles. The IP6/ β -TCP cement specimens with PLGA particles had excellent material properties, such as injectability, compressive strength, high porosity, no cytotoxicity in vitro, bioresorption and bone formation abilities in vivo . Organic-inorganic hybridized CPCs are expected to be valuable as novel biodegradable paste-like artificial bone fillers. Graphical abstract: uf0001